Electrolyte and lithium battery
By introducing functional additives into the electrolyte to form a stable CEI film, the circulation capacity and voltage attenuation of high-voltage lithium batteries are solved, the circulation stability and lithium ion utilization efficiency of lithium batteries are improved, and internal resistance and safety risks are reduced.
Patent Information
- Application Number
- CN202411310782.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-10
AI Technical Summary
During the charging and discharging cycle of high-voltage lithium batteries, the increase in the electrode potential of the positive electrode material leads to the oxidation and decomposition of the electrolyte and the intensification of the interface reaction, resulting in an increase in the internal resistance of the battery and a decrease in performance. The existing modified positive electrode materials have a complex process and high cost. Difficult to industrially apply.
Introduce specific functional additives into the electrolyte to form a stable CEI film, neutralize acidic substances through nitrogen atoms in the pyrimidine, eliminate water and hydrofluoric acid through silicon oxygen bonds, reduce internal resistance, and form dense and uniform through unsaturated bonds CEI film protects the positive electrode interface, inhibits side reactions, and improves the power characteristics of lithium ion transmission.
It significantly improves the circulation stability and lithium ion utilization efficiency of lithium batteries, extends the circulation capacity and voltage stability of the battery, and reduces the internal resistance and safety risks of the battery.
Smart Images

Figure CN119297400A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular, relates to an electrolyte and a lithium battery. Background Art
[0002] The continued prosperity of computers, communications and consumer electronics has brought about the rapid development of the lithium battery industry. In particular, the rise of new energy vehicles in recent years has not only promoted the development of power lithium batteries, but also put forward higher energy density and safety performance. The endurance of electric vehicles has become one of the performance indicators that consumers are most concerned about, and the energy density of the battery determines the single mileage of electric vehicles. How to improve the energy density of the battery under limited space and weight has become a hot topic of research by all parties. Increasing the working voltage of the positive electrode material is a major way to improve the energy density of lithium batteries. At present, high-voltage positive electrode materials, such as lithium nickel manganese oxide (LNMO), high-voltage ternary, high-voltage lithium cobalt oxide, layered lithium-rich oxide (LLO), etc. have become research hotspots. As the voltage of lithium batteries continues to increase, the positive electrode material will have a higher electrode potential, the oxidation decomposition of the electrolyte at the positive electrode and the positive electrode interface reaction will be more intense, and as the battery charge and discharge cycle continues, the internal resistance of the battery gradually increases, which in turn causes the battery performance to decline or even fail.
[0003] At present, researchers mainly overcome these defects by modifying the cathode material or adjusting the electrolyte formula. However, the cathode material modification method is complex and costly, while adjusting the electrolyte formula is simple to operate, has obvious effects, and is conducive to industrial application. Therefore, how to adjust the electrolyte formula to improve the interface stability between the electrolyte and the cathode is a technical problem that technicians in this field need to solve urgently in their research. Summary of the invention
[0004] The purpose of the present invention is to provide an electrolyte, in which the functional additives can form a stable CEI film on the positive electrode surface and in situ regulate the chemical composition of the CEI film, thereby effectively protecting the positive electrode interface and making the lithium battery using the electrolyte have excellent cycle stability and lithium ion utilization efficiency.
[0005] According to one aspect of the present invention, an electrolyte is provided, comprising a lithium salt, an organic solvent and an electrolyte additive, wherein the electrolyte additive comprises a functional additive, and the structure of the functional additive is as shown in Formula I;
[0006]
[0007] R1 and R2 are independently selected from hydrogen, C1-10 straight chain or branched alkyl or alkoxy, and C1-10 halogenated straight chain or branched alkyl or alkoxy.
[0008] The present invention introduces a functional additive having a structure as shown in Formula I into the electrolyte, wherein the nitrogen atom on the pyrimidine in the structure of the functional additive can neutralize the acidic substances (PF5, HF, CO2, etc.) in the electrolyte; at the same time, the silicon-oxygen bond in the structure of the functional additive can eliminate water and hydrofluoric acid in the electrolyte, thereby improving the stability of the electrolyte, reducing the internal resistance of the electrolyte, and improving the charge-discharge performance and safety performance of the battery; moreover, the unsaturated bonds in the structure of the functional additive can be oxidized to form a dense and uniform CEI film on the surface of the positive electrode, thereby protecting the positive electrode interface, being beneficial to inhibiting the dissolution of transition metal ions and the release of oxygen, reducing the side reaction between the electrolyte and the positive electrode interface, and improving the stability of the interface; and the formed CEI film can promote the rapid transmission of lithium ions in the electrolyte and on the surface of the positive electrode, thereby improving the lithium ion transmission dynamic characteristics and cycle stability of the battery.
[0009] In summary, the present invention adopts specific functional additives as electrolyte additives to form a stable CEI film on the positive electrode surface and in situ regulate the chemical composition of the CEI film, which effectively protects the positive electrode interface and solves the problems of rapid capacity decay and voltage decay in high-voltage material system batteries, thereby enabling the battery to have excellent cycle characteristics and lithium ion utilization efficiency.
[0010] Preferably, the mass proportion of the functional additive in the electrolyte is 0.3% to 1.0%. By controlling the content of the functional additive in the electrolyte, it is beneficial for the functional additive to form a dense and uniform CEI film on the positive electrode surface, preventing the problem of excessive film formation causing the battery impedance to increase and the cycle performance to decrease, thereby further improving the cycle stability of the battery.
[0011] Preferably, the electrolyte additives also include sulfur-containing additives, carbonate additives and lithium salt additives. The introduction of the above additives is conducive to promoting the formation of a good CEI film on the positive electrode surface, thereby improving the structural stability and cycle stability of the battery.
[0012] Preferably, the sulfur-containing additive includes at least one of 1,3-propane sultone, methylene disulfonate, and vinyl sulfate; the carbonate additive includes at least one of vinylene carbonate and ethylene carbonate; the lithium salt additive includes at least one of lithium bis(trifluoromethane)sulfonyl imide, lithium difluorooxalate borate, and lithium difluorooxalate phosphate. The above-mentioned specific sulfur-containing additives and lithium salt additives can assist the above-mentioned functional additives in forming a good CEI film on the positive electrode surface and ensure the compactness and stability of the generated CEI film; at the same time, the above-mentioned specific sulfur-containing additives, lithium salt additives, and carbonate additives can work together to promote the formation of a good SEI film on the negative electrode surface. Therefore, the above-mentioned specific carbonate additives, lithium salt additives, sulfur-containing additives, and functional additives can play a synergistic role and improve the interfacial stability between the electrolyte and the positive and negative electrodes; in addition, the stability and density of the CEI film can be improved, the dissolution of positive electrode metal ions can be effectively inhibited, and the damage of metal ions to the CEI film can be weakened, so that the cycle stability of the battery and the effective utilization rate of lithium ions can be further improved.
[0013] Preferably, the sulfur-containing additive includes 1,3-propane sultone; the carbonate additive includes vinyl ethylene carbonate; and the lithium salt additive includes lithium bis(trifluoromethane)sulfonyl imide.
[0014] Preferably, the mass proportion of sulfur-containing additives in the electrolyte is 0.5% to 1.0%; the mass proportion of carbonate additives in the electrolyte is not higher than 0.5%; the mass proportion of lithium salt additives in the electrolyte is 0.5% to 1.0%; the mass proportion of functional additives in the electrolyte is 0.3% to 1.0%. By controlling the content of carbonate additives, lithium salt additives, sulfur-containing additives, and functional additives within a reasonable range, it is beneficial for the components of the electrolyte additives to fully play a synergistic role, improve the interface stability between the electrolyte and the positive and negative electrode surfaces, and avoid the problem of increased battery impedance caused by excessive film formation, thereby improving the cycle stability of the battery system.
[0015] Preferably, the organic solvent includes cyclic carbonates, chain carbonates and chain carboxylates.
[0016] Preferably, calculated by mass ratio, cyclic carbonate: chain carbonate: chain carboxylate = 1-20: 15-70: 5-20. The synergistic combination of cyclic carbonate, chain carbonate and chain carboxylate in the organic solvent can, on the one hand, inhibit the decomposition of the electrolyte under high temperature environment and reduce the occurrence of side reactions between the electrode material and the electrolyte. At the same time, it can promote the rapid transmission of lithium ions in the electrolyte under low temperature environment, so that the electrolyte can be used in a working environment with a wide temperature range, giving the lithium battery good high and low temperature charge and discharge performance; on the other hand, the above-mentioned organic solvent has the advantages of high dielectric constant and low viscosity, which can promote the dissolution and dispersion of lithium salts and electrolyte additives, so that each component of the electrolyte can fully play its own advantages, ensure the compactness and uniformity of the CEI film formed on the surface of the positive electrode, and further improve the electrochemical performance of the battery.
[0017] Preferably, the cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate and propylene carbonate.
[0018] Preferably, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.
[0019] Preferably, the chain carboxylic acid ester includes at least one of methyl formate, methyl acetate, and ethyl difluoroacetate.
[0020] Preferably, in the electrolyte, the content of lithium salt is 12 wt% to 18 wt%, the content of organic solvent is 80 wt% to 86 wt%, and the content of electrolyte additives does not exceed 5 wt%.
[0021] According to another aspect of the present invention, a lithium battery is provided, comprising the above-mentioned electrolyte. The lithium battery provided by the present invention can form a good CEI film on the positive electrode surface by using the above-mentioned electrolyte, improve the interface stability between the electrolyte and the positive electrode, and significantly optimize the normal temperature and high temperature cycle characteristics of the lithium battery using the electrolyte. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0023] Example 1
[0024] Treatment Group 1-1
[0025] The processing group provides an electrolyte solution, which consists of an organic solvent, a lithium salt and an electrolyte additive.
[0026] The electrolyte additives include sulfur-containing additives, carbonate additives, lithium salt additives and functional additives. The content of the electrolyte additives in the electrolyte is 1.4wt%.
[0027] The carbonate additive is vinyl ethylene carbonate (VEC), and the mass proportion of VEC in the electrolyte is 0.2%;
[0028] The lithium salt additive is lithium bis(fluorosulfonyl)imide (LiFSI), and the mass proportion of LiFSI in the electrolyte is 0.4%;
[0029] The sulfur-containing additive is 1,3-propane sultone (PS), and the mass proportion of PS in the electrolyte is 0.5%;
[0030] The functional additive is 2,4-bis(trimethylsilyloxy)pyrimidine, and its structure is shown in Formula II;
[0031] The mass percentage of functional additives in the electrolyte is 0.3%;
[0032] The lithium salt is lithium hexafluorophosphate, and the content of lithium hexafluorophosphate in the electrolyte is 14 wt %.
[0033] The content of organic solvent in the electrolyte is 84.4wt%. Based on the total mass of organic solvent as 100%, the organic solvent is composed of 20% cyclic carbonate (5% fluoroethylene carbonate, 15% ethylene carbonate), 70% chain carbonate (diethyl carbonate), and 10% chain carboxylic acid ester (ethyl difluoroacetate).
[0034] The electrolyte provided by the treatment group is prepared by the following steps: under an argon atmosphere, an electrolyte additive is added to an organic solvent, and then a lithium salt is added, and the mixture is stirred and mixed at 10° C. to prepare an electrolyte.
[0035] Treatment Group 1-2
[0036] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the structure of the functional additive in this treatment group is shown in formula III;
[0037]
[0038] Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.
[0039] Treatment Groups 1-3
[0040] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the structure of the functional additive in this treatment group is shown in formula IV;
[0041]
[0042] Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.
[0043] Treatment Groups 1-4
[0044] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the structure of the functional additive in this treatment group is shown in formula V;
[0045]
[0046] Except for the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.
[0047] Treatment Groups 1-5
[0048] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the mass proportion of the functional additive in the electrolyte in this treatment group is 0.2%. In addition to the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.
[0049] Treatment Groups 1-6
[0050] This treatment group prepared the electrolyte with reference to treatment group 1-1. The difference between this treatment group and treatment group 1-1 is that the mass proportion of the functional additive in the electrolyte in this treatment group is 1.2%. In addition to the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.
[0051] Treatment Groups 1-7
[0052] This treatment group prepared the electrolyte with reference to treatment group 1-1, and the difference between this treatment group and treatment group 1-1 is that the organic solvent used in this treatment group does not include chain carboxylic acid ester. In addition to the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.
[0053] Treatment Groups 1-8
[0054] This treatment group prepared the electrolyte with reference to treatment group 1-1. The difference between this treatment group and treatment group 1-1 is that the mass ratio of cyclic carbonate, chain carbonate and chain carboxylic acid ester in the organic solvent used in this treatment group is 27:70:3. In addition to the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 1-1.
[0055] Treatment Groups 1-9
[0056] The electrolyte of this treatment group was prepared by referring to the treatment group 1-1. The difference between this treatment group and the treatment group 1-1 is that the mass ratio of cyclic carbonate, chain carbonate and chain carboxylic acid ester in the organic solvent used in this treatment group is 1:70:29. In addition to the above differences, the materials and process operations used in this treatment group are strictly consistent with those of the treatment group 1-1.
[0057] Comparative treatment group 1-1
[0058] The electrolyte of this comparative treatment group is prepared by referring to treatment group 1-1. The difference between this embodiment and treatment group 1-1 is that the electrolyte additives used in this comparative treatment group do not include functional additives. In addition to the above differences, the materials and process operations used in this embodiment are strictly consistent with those of treatment group 1-1.
[0059] Comparative treatment group 1-2
[0060] The electrolyte of this comparative treatment group was prepared with reference to treatment group 1-1. The difference between this comparative treatment group and treatment group 1-1 is that the structure of the functional additive in this comparative treatment group is shown in formula VII;
[0061]
[0062] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 1-1.
[0063] Comparative treatment groups 1-3
[0064] The electrolyte of this comparative treatment group is prepared by referring to treatment group 1-1. The difference between this comparative treatment group and treatment group 1-1 is that the structure of the functional additive in this comparative treatment group is shown in formula VIII;
[0065]
[0066] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 1-1.
[0067] Example 2
[0068] Treatment Group 2-1
[0069] This treatment group prepared the electrolyte according to treatment group 1-1, and the materials and process operations used in this treatment group were strictly consistent with those of treatment group 1-1.
[0070] Treatment group 2-2
[0071] This treatment group prepared the electrolyte with reference to treatment group 2-1. The difference between this treatment group and treatment group 2-1 is that the same mass of vinyl sulfate (DTD) was used in this treatment group to replace PS in treatment group 2-1 as the sulfur-containing additive. In addition to the above differences, the materials and process operations used in this treatment group are strictly consistent with those of treatment group 2-1.
[0072] Treatment Group 2-3
[0073] The electrolyte of this treatment group was prepared by referring to treatment group 2-1. The difference between this treatment group and treatment group 2-1 is that the same mass of lithium difluoro oxalophosphate (LiODFP) was used in this treatment group to replace LiFSI in treatment group 2-1 as a lithium salt additive. In addition to the above differences, the materials and process operations used in this treatment group were strictly consistent with those of treatment group 2-1.
[0074] Treatment Groups 2-4
[0075] This treatment group prepared the electrolyte with reference to treatment group 2-1. The difference between this treatment group and treatment group 2-1 is that the same mass of ethylene sulfite (ES) was used in this treatment group to replace PS in treatment group 2-1 as the sulfur-containing additive. In addition to the above differences, the materials and process operations used in this treatment group were strictly consistent with those of treatment group 2-1.
[0076] Treatment Groups 2-5
[0077] The electrolyte of this treatment group was prepared by referring to treatment group 2-1. The difference between this treatment group and treatment group 2-1 is that the same mass of lithium bis(oxalatoborate) (LiBOB) was used as a lithium salt additive instead of LiFSI in treatment group 2-1. In addition to the above differences, the materials and process operations used in this treatment group were strictly consistent with those of treatment group 2-1.
[0078] Comparative treatment group 2-1
[0079] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-1. The difference between this comparative treatment group and treatment group 2-1 is that the structure of the functional additive in this comparative treatment group is shown in formula VI;
[0080]
[0081] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-1.
[0082] Comparative treatment group 2-2
[0083] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-2. The difference between this comparative treatment group and treatment group 2-2 is that the structure of the functional additive in this comparative treatment group is shown in formula VI;
[0084]
[0085] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-2.
[0086] Comparative treatment group 2-3
[0087] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-3. The difference between this comparative treatment group and treatment group 2-3 is that the structure of the functional additive in this comparative treatment group is shown in formula VI;
[0088]
[0089] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-3.
[0090] Comparative treatment groups 2-4
[0091] The electrolyte of this comparative treatment group was prepared with reference to treatment group 2-4. The difference between this comparative treatment group and treatment group 2-4 is that the structure of the functional additive in this comparative treatment group is shown in formula VI;
[0092]
[0093] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment groups 2-4.
[0094] Comparative treatment groups 2-5
[0095] The electrolyte of this comparative treatment group was prepared with reference to treatment group 2-5. The difference between this comparative treatment group and treatment group 2-5 is that the structure of the functional additive in this comparative treatment group is shown in formula VI;
[0096]
[0097] Except for the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment groups 2-5.
[0098] Comparative treatment groups 2-6
[0099] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-1. The difference between this comparative treatment group and treatment group 2-1 is that the functional additive in treatment group 2-1 was replaced by the same mass of film-forming additive fluoroethylene carbonate (FEC). In addition to the above differences, the materials and process operations used in this comparative treatment group were strictly consistent with those of treatment group 2-1.
[0100] Comparative treatment groups 2-7
[0101] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-2. The difference between this comparative treatment group and treatment group 2-2 is that the functional additive in treatment group 2-2 was replaced by the same mass of film-forming additive fluoroethylene carbonate (FEC) in this comparative treatment group. In addition to the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-2.
[0102] Comparative treatment groups 2-8
[0103] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-3. The difference between this comparative treatment group and treatment group 2-3 is that the functional additive in treatment group 2-3 was replaced by the same mass of film-forming additive fluoroethylene carbonate (FEC) in this comparative treatment group. In addition to the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-3.
[0104] Comparative treatment groups 2-9
[0105] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-4. The difference between this comparative treatment group and treatment group 2-4 is that the functional additive in treatment group 2-4 was replaced by the same mass of film-forming additive fluoroethylene carbonate (FEC). In addition to the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-4.
[0106] Comparative treatment group 2-10
[0107] The electrolyte of this comparative treatment group was prepared by referring to treatment group 2-5. The difference between this comparative treatment group and treatment group 2-5 is that the functional additive in treatment group 2-5 was replaced by the same mass of film-forming additive fluoroethylene carbonate (FEC) in this comparative treatment group. In addition to the above differences, the materials and process operations used in this comparative treatment group are strictly consistent with those of treatment group 2-5.
[0108] Test Example 1
[0109] 1. Test object: A lithium battery was prepared using the electrolyte prepared in Examples 1 to 2. The preparation method of the lithium battery was as follows: a negative electrode material graphite, a conductive agent acetylene black, and a binder CMC and SBR were prepared in a mass percentage of 94:1:2:3 to form a negative electrode slurry, which was coated on a copper foil current collector and vacuum dried to obtain a negative electrode sheet; a positive electrode material 0.25Li2MnO3·0.75LiMn 0.375 Ni 0.375 Co 0.25 O2, conductive agent acetylene black and binder PVDF were prepared into positive electrode slurry in a mass ratio of 94:3:3 and coated on the aluminum foil current collector, and vacuum dried to obtain positive electrode sheets. The positive electrode sheets, negative electrode sheets, Celgard2400 separators and electrolytes were assembled into soft-pack batteries. The obtained batteries were used as the test objects of this test example.
[0110] 2. Test items:
[0111] (1) Normal temperature cycle performance test:
[0112] At 25°C, the lithium-ion battery is charged at a constant current of 0.5C (nominal capacity) to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery is charged and discharged 1000 times at 25°C under the above conditions.
[0113] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.
[0114] The average voltage (V) of a lithium-ion battery after N cycles = discharge energy of the Nth cycle / discharge capacity of the Nth cycle, where N is the number of cycles of the lithium-ion battery.
[0115] (2) High temperature cycle performance test:
[0116] At 45°C, the lithium-ion battery is charged at a constant current of 1.0C (nominal capacity) to a voltage of 4.6V, then charged at a constant voltage of 4.6V to a current ≤ 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.5V. The above is one charge and discharge cycle. The lithium-ion battery is subjected to 800 charge and discharge cycles at 45°C under the above conditions.
[0117] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.
[0118] The average voltage (V) of a lithium-ion battery after N cycles = discharge energy of the Nth cycle / discharge capacity of the Nth cycle, where N is the number of cycles of the lithium-ion battery.
[0119] 3. Test results:
[0120] Table 1. Performance test results of Example 1
[0121]
[0122]
[0123] The test results are shown in Table 1. The performance test results of treatment group 1-1 were compared with those of comparison treatment groups 1-1 to 1-3. As shown in Table 1, under the same conditions of other materials and operations for preparing the battery, the electrolyte additives used in comparison treatment group 1-1 do not include functional additives, the functional additives used in comparison treatment group 1-2 do not contain silicon-oxygen bonds, and the functional additives used in comparison treatment group 1-3 do not contain pyrimidine structures. The cycle capacity retention rate and average voltage of the battery prepared in this way at 25°C and 45°C are lower than those of treatment group 1-1. This shows that, compared with the control treatment groups 1-1 to 1-3, the treatment group 1-1 introduces a functional additive having a structure as shown in Formula I into the electrolyte, and the nitrogen atom on the pyrimidine in the structure of the functional additive can neutralize the acidic substances (PF5, HF, CO2, etc.) in the electrolyte; at the same time, the silicon-oxygen bond in the structure of the functional additive can eliminate water and hydrofluoric acid in the electrolyte, improve the stability of the electrolyte, reduce the internal resistance of the electrolyte, and improve the charge and discharge performance and safety performance of the battery; moreover, the unsaturated bonds in the above-mentioned functional additive structure can be oxidized to form a dense and uniform CEI film on the positive electrode surface, which protects the positive electrode interface, is beneficial to inhibit the dissolution of transition metal ions and the release of oxygen, reduces the side reactions between the electrolyte and the positive electrode interface, and improves the stability of the interface. The formed CEI film can promote the rapid transmission of lithium ions in the electrolyte and the positive electrode surface, thereby improving the normal high temperature cycle performance and lithium ion utilization efficiency of the battery.
[0124] Comparing the performance test results of treatment groups 1-1 to 1-4 and treatment groups 1-5 to 1-6 in Example 1, it can be found that the cycle capacity retention rate and average voltage at 25°C and 45°C of the batteries prepared from treatment groups 1-5 to 1-6 are lower than those of treatment groups 1-1 to 1-4. The reason is that under the same conditions of other materials and operations for preparing the battery, the mass proportion of the functional additives in the electrolyte in treatment group 1-5 is relatively low, which is not conducive to the formation of a dense and uniform CEI film of the functional additives on the surface of the positive electrode, thereby deteriorating the normal high temperature cycle performance and average voltage of the battery; the mass proportion of the functional additives in the electrolyte in treatment group 1-6 is relatively high, and excessive film formation leads to increased impedance of the battery, and deterioration of the normal high temperature cycle performance and average voltage.
[0125] Comparing the performance test results of treatment groups 1-1 to 1-4 and treatment groups 1-7 to 1-9 in Example 1, it can be found that the cycle capacity retention rate and average voltage of the batteries prepared from treatment groups 1-7 to 1-9 at 25°C and 45°C are lower than those of treatment groups 1-1 to 1-4. The reason is that under the same conditions of other materials and operations for preparing the battery, the organic solvent used in treatment group 1-7 does not include chain carboxylic acid esters, and the mass ratio of cyclic carbonates, chain carbonates, and chain carboxylic acid esters in the organic solvents used in treatment groups 1-8 and 1-9 does not meet 1-20:15-70:5-20, and cyclic carbonates, chain carbonates, and chain carboxylic acid esters are difficult to play a synergistic role, thereby deteriorating the normal high temperature cycle performance and average voltage of the battery.
[0126] Table 2. Performance test results of Example 2
[0127]
[0128]
[0129] The test results are shown in Table 2. The treatment groups 2-1 to 2-5 were compared. The treatment group 2-1 used VEC, LiFSI, PS and 2,4-bis(trimethylsiloxy)pyrimidine as electrolyte additives, the treatment group 2-2 used VEC, LiFSI, DTD and 2,4-bis(trimethylsiloxy)pyrimidine as electrolyte additives, the treatment group 2-3 used VEC, LiODFP, PS and 2,4-bis(trimethylsiloxy)pyrimidine as electrolyte additives, the treatment group 2-4 used VEC, LiFSI, ES and 2,4-bis(trimethylsiloxy)pyrimidine as electrolyte additives, and the treatment group 2-5 used VEC, LiBOB, PS and 2,4-bis(trimethylsiloxy)pyrimidine as electrolyte additives. It can be seen from Table 2 that in terms of the cycle capacity retention rate and average voltage at 25°C and 45°C, the treatment group 2-1>treatment group 2-2, treatment group 2-3>treatment group 2-4, treatment group 2-5. Further, by comparing the treatment groups 2-1 to 2-5 with the comparative treatment groups 2-1 to 2-5, it can be found that under the same conditions of other materials and operations for preparing lithium batteries, the difference between the treatment group 2-1 and the comparative treatment group 2-1, the treatment group 2-2 and the comparative treatment group 2-2, the treatment group 2-3 and the comparative treatment group 2-3, the treatment group 2-4 and the comparative treatment group 2-4, and the treatment group 2-5 and the comparative treatment group 2-5 is only the functional additives, however, in terms of the values of the cycle capacity retention rate and the average voltage at 25°C and 45°C, the comparative treatment groups 2-1 to 2-5 are relatively close. The reason is that compared with the functional additives shown in Formula I, the compound shown in Formula VI (structural analogues of Formula I) cannot play a synergistic role with specific lithium salt additives, carbonate additives, and sulfur-containing additives, and is not enough to further improve the cycle stability and lithium ion utilization efficiency of the battery.
[0130] Similarly, the treatment groups 2-1 to 2-5 are compared with the comparative treatment groups 2-6 to 2-10. It can be seen from Table 2 that the lithium batteries prepared by the comparative treatment groups 2-6 to 2-10 are close in the values of cycle capacity retention and average voltage at 25°C and 45°C. The reason is that compared with the functional additives shown in Formula I, FEC (functional analogue of Formula I) cannot play a synergistic role with specific lithium salt additives, carbonate additives, and sulfur-containing additives, and is not enough to further improve the cycle stability of the battery. This shows that the functional additives shown in Formula I can play a synergistic role with specific sulfur-containing additives (such as PS), carbonate additives (such as VEC), and lithium salt additives (such as LiFSI), promote the formation of CEI film, and further improve the cycle characteristics of the battery and the effective utilization rate of lithium ions.
[0131] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: It includes a lithium salt, an organic solvent and an electrolyte additive, wherein the electrolyte additive includes a functional additive, and the structure of the functional additive is shown in Formula I; R1 and R2 are independently selected from hydrogen, C1-10 straight chain or branched alkyl or alkoxy, and C1-10 halogenated straight chain or branched alkyl or alkoxy.
2. The electrolyte according to claim 1, characterized in that The functional additive accounts for 0.3% to 1.0% by mass in the electrolyte.
3. The electrolyte according to claim 1, characterized in that The electrolyte additives also include sulfur-containing additives, carbonate additives and lithium salt additives.
4. The electrolyte according to claim 3, characterized in that The sulfur-containing additive includes at least one of 1,3-propane sultone, methylene methane disulfonate, and vinyl sulfate; The carbonate additive includes at least one of vinylene carbonate and vinyl ethylene carbonate; The lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, and lithium difluorooxalatophosphate.
5. The electrolyte according to claim 4, characterized in that The sulfur-containing additive includes the 1,3-propane sultone; the carbonate additive includes the vinyl ethylene carbonate; and the lithium salt additive includes the lithium bis(trifluoromethane)sulfonyl imide.
6. The electrolyte according to claim 4, characterized in that The mass percentage of the sulfur-containing additive in the electrolyte is 0.5% to 1.0%; The mass percentage of the carbonate additive in the electrolyte is no more than 0.5%; The mass percentage of the lithium salt additive in the electrolyte is 0.5% to 1.0%; The functional additive accounts for 0.3% to 1.0% by mass in the electrolyte.
7. The electrolyte according to claim 1, characterized in that The organic solvent includes cyclic carbonates, chain carbonates and chain carboxylates.
8. The electrolyte according to claim 7, characterized in that Calculated by mass ratio, the cyclic carbonate: the chain carbonate: the chain carboxylate = 1-20: 15-70: 5-20.
9. The electrolyte according to any one of claims 1 to 8, characterized in that: In the electrolyte, the content of the lithium salt is 12wt% to 18wt%, the content of the organic solvent is 80wt% to 86wt%, and the content of the electrolyte additive does not exceed 5wt%.
10. A lithium battery, characterized in that: Comprising the electrolyte as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Electrolyte and lithium ion battery containing same
CN105680096A
Lithium ion battery electrolyte and lithium ion battery prepared therefrom
CN108306048A
Electrolyte additive, electrolyte and lithium secondary battery
CN113956282A
Electrolyte additive, lithium ion battery electrolyte applying electrolyte additive and lithium ion battery
CN116014248A
Electrolyte and preparation method and application thereof
CN117039158A
Cited By
Electrolyte additive composition, electrolyte and battery
CN119786736A